Sosialisasi Penggunaan Media Sosial yang Bijak Dan Aman di Madrasah Aliyah - Novi Ismiasih; Ach Nurhamid Awalluddin2 (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
Social media is a digital platform that allows users to interact with others through digital content. Social media has become an important part of everyone's life, with social media someone can find and follow people, follow news and share information from others. However, the use of social media also has several risks, such as opening up opportunities for negative behavior and increasing privacy risks. Therefore, a wise and safe attitude is needed in using social media. Community Service at Madrasah Aliyah Fathul Hidayah aims to improve students' understanding of the use of social media wisely and safely. This activity will involve training and discussion sessions on the benefits and risks of using social media, how to choose the right social media platform